Meso-Complexity Computer Simulation Investigation on Antiexplosion Performance of Double-Layer Foam Aluminum under Pore Grading - Zhen Wang; Wen Bin Gu; Xing Bo Xie; Yu Tian Chen; Lei Fu (Complexity)
Foam aluminum is an energy-absorbing material with excellent performance. The interlayer composed of multiple layers of foam aluminum and steel plate has good antiexplosion ability. In order to explore the antiexplosion performance of double-layer foam aluminum under different porosity rankings and to reveal its microscopic deformation law and failure mechanism, three kinds of aluminum foams with a porosity of 80%, 85%, and 90% were selected to form six different structures. Based on the Voronoi algorithm, a three-dimensional foam aluminum generation algorithm with random pore size and random wall thickness was written by using the Python language and Fortran language. The three-dimensional mesoscopic model of double-layer closed-cell aluminum foam sandwich panel is established by using LS-DYNA and ABAQUS software. The explosion process was simulated, and the flow field movement of explosion shock wave of aluminum foam under different porosity rankings was analyzed. Two groups of aluminum foam were randomly selected for the explosion test and compared for the strain and compression. The test results are consistent with the simulation results, which verifies the correctness of the three-dimensional meso-model. The results show that when the porosity of the upper layer of aluminum foam is greater than that of the lower layer of aluminum foam, the sandwich structure of double-layer aluminum foam has a large compression and the bottom plate has a small displacement; it is not that the greater the compression amount of aluminum foam is, the better the antiexplosion and wave absorption ability is. When the aluminum foam reaches the ultimate load-bearing capacity, the aluminum foam transfers the load due to compaction, resulting in stress enhancement phenomena. Through the analysis of the compression amount, floor deformation, wave dissipation capacity, and energy ratio of aluminum foam, it is concluded that the antiexplosion wave absorption effect of the sandwich structure of aluminum foam with 80%/85% group is the best; the changes of porosity and cell wall are important factors affecting the energy absorption capacity of aluminum foam.